Uji Kerja Mesin Pencacah Kulit Kelapa Berdasarkan Perbedaan Puli - Ali Hasimi Pane; N. Saputra; Tengku Jukdin Saktisahdan (CV. IRA PUBLISHING, 2023)
Coconut husk, currently processed into coco fibre and cocopeat is the highest percentage of coconut fruit waste. A coconut husk chopping machine is a machine that can chop coconut husk so that it can then be utilized as a planting medium. Pulley has a function to receive power transmitted from the drive engine to the blade shaft. Pulley diameter variations are carried out to determine the data on the pulley rotation, chopping time, and fuel consumption results. This study used a pulley with a diameter of 3 inches (76mm), 5 inches (127mm), dan 7 inches (178mm). The most optimal rotation is on the 3-inch diameter pulley with 3600 Rpm; the fastest chopping time is on the 3-inch pulley with a duration of 748 seconds; the pulley with the most chopped results is on a 3-inch pulley, which is 1.780 kg. And pulley with the least unshredded results is a 3-inch diameter pulley of 0.220 kg.